Financial Statement Preparation Skills for Business Actors Using Applications - Edan, Thamir Salih (Akademi Sertifikasi Profesi Internasional, 2023)
The digital era that is full of technological developments must be utilized to increase the profits of micro and small businesses. One of the efforts is to utilize an android application to record transactions. Some business actors do not understand the use of this application. The purpose of this community service is to increase awareness and skills of business actors in utilizing the android-based financial application